Translation and Adaptation of Carolina Premenstrual Assessment Scoring System (Journal of Asian Development Studies, 2025)
Premenstrual dysphoric disorder (PMDD) is a severe and enervating premenstrual mood disturbance with a wide variety of symptoms, including depression, anxiety, lack of interest in life, tearfulness, irritability, anger, difficulty in concentration, appetite changes, weight gain, muscle and joint pain, sleep disturbance, and suicidal thoughts (Huston & Fujitsubo, 2002). The present study aimed to translate the Carolina Premenstrual Assessment Scoring System into Urdu. For this purpose, the study was carried out in two steps. Step 1 used MAPI guidelines for translating psychometric measures into Urdu Language. In step 2, the a priori method was used to establish the construct validity of the Carolina Premenstrual Assessment Scoring System.